The role of water on the structure and mechanical properties of a thermoplastic natural block co-polymer from squid sucker ring teeth - Rieu, Clément (2017)
Hard biological polymers exhibiting a truly thermoplastic behavior that can maintain their structural properties after processing are extremely rare and highly desirable for use in advanced technological applications such as 3D-printing, biodegradable plastics and robust composites. One exception are the thermoplastic proteins that comprise the sucker ring teeth (SRT) of the Humboldt jumbo squid (Dosidicus gigas). In this work, we explore the mechanical properties of reconstituted SRT proteins and demonstrate that the material can be re-shaped by simple processing in water and at relatively low temperature (below 100 °C). The post-processed material maintains a high modulus in the GPa range, both in the dry and the wet states. When transitioning from low to high humidity, the material properties change from brittle to ductile with an increase in plastic deformation, where water acts as a plasticizer. Using synchrotron x-ray scattering tools, we found that water mostly influences nano scale structure, whereas at the molecular level, the protein structure remains largely unaffected. Furthermore, through simultaneous in situ x-ray scattering and mechanical tests, we show that the supramolecular network of the reconstituted SRT material exhibits a progressive alignment along the strain direction, which is attributed to chain alignment of the amorphous domains of SRT proteins. The high modulus in both dry and wet states, combined with their efficient thermal processing characteristics, make the SRT proteins promising substitutes for applications traditionally reserved for petroleum-based thermoplastics.